THE MAIN CRITERIA FOR THE EFFECTIVE USE OF RESOURCE POTENTIAL IN ENSURING NATIONAL COMPETITIVENESS: https://doi.org/10.5281/zenodo.16778003 - Khudoyberdiyev , Dilmurod (Science technology&Digital finance, 2025)
This article analyzes the economic and environmental criteria for the effective use of resource potential in increasing national competitiveness in the economy of Uzbekistan. Full mobilization of resource capacity is seen as an important factor in ensuring competitiveness by reducing production costs, lowering product cost, and increasing utility. Advanced methods of assessing resource utilization based on theoretical approaches by the author, Porter, Kaplan, and prominent scientists such as Norton, Barney, Drucker, Elkington, have been studied. The article also covers the existing practices on the use of resources in Uzbekistan and strategic approaches based on innovative technologies. The focus is on criteria such as resource conservation, sustainable management, economic efficiency, environmental compliance, and the introduction of innovative technologies. These approaches will serve to ensure Uzbekistan’s sustainable economic growth and competitiveness in the global market.